NMR Facies Definition for Permo-Triassic Kangan/Dalan Carbonate Formation by Use of Core/Log and Pore-Scale Measurements - Mardani, A.; Rezaee, M. Reza; Eskandar, A. (Society of Petroleum Engineers, 2013)
An integrated and quantitative approach is taken here to the Permo-Triassic Kangan/Dalan carbonate formation. We apply pore-network characterization to the problem of the classification of these complex carbonate gas-reservoir rocks. We start with the useful and convenient nuclear-magnetic-resonance (NMR) data on 28 samples to define NMR facies (NMRF). The NMRF grouping is performed with both the relaxivity constant (q2) and the specific-surface-volume (Sgv) data. Seven NMRF have been defined with a combination of core/log NMR data, petrographic image analysis, and mercury-injection examinations for two wells. The advantage of evaluation of the pore spaces rather than grain properties is to discover trends that are not apparent when one uses a conventional sedimentological facies definition. Lithology- independent NMRF exhibit properties that are associated with pore geometry. This should have special importance for the formation evaluation of carbonates.